Identity Politics and Religions: The Detrimental Effects on The ASEAN Regional Stability - Kurniawan Netanyahu; Lelly Sepniwati (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Identity politics and religion pose significant challenges for many countries in Southeast Asia, potentially threatening regional stability. Despite this, there has been limited research exploring their impact on regional stability in ASEAN countries. A recent study aimed to analyze the influence of identity politics and religion in ASEAN member countries, particularly those with democratic systems such as Indonesia, Malaysia, Singapore, the Philippines, and Thailand, from 2020 to 2024. The research used a descriptive qualitative approach, examining annual reports on freedom of religion and belief, domestic political and economic dynamics, as well as previous and current literature on political, economic, and social dynamics in the region. The analysis revealed that Indonesia, Malaysia, Singapore, the Philippines, and Thailand are experiencing domestic instability, partly due to identity politics and religion. The research found that the majority ethnic or religious groups dominate identity and religious politics with support from the government and political elites, leading to regional instability within ASEAN member countries. Additionally, it was noted that national regulations need updating, particularly regarding equality and justice for minority groups and the mass media, to address the suppression of identity politics and religion in democratic systems.